Managing policy lapse risk in Sweden's life insurance market between 1915 and 1947. Issue 2 (17th February 2020) - Adams, Mike; Andersson, Lars-Fredrik; Lindmark, Magnus; Eriksson, Liselotte; Veprauskaite, Elena
Abstract: We examine the challenges that Swedish life insurers faced in managing the lapse risk of policies written on the lives of the industrial urban working class between 1915 and 1947. We observe that with the threat of State socialisation of insurance in the 1930s, industrial life insurers modified their business practices to better control policy lapses. Using firm-level data, we also analyse the effect of socio-economic changes, such as rising real wages, interest rate fluctuations and unemployment on life insurance policy lapses. Our results support contemporary tests of the emergency fund and interest rate explanations for the voluntary premature termination of life insurance policies.